The Effect of Managerial Attitudes on Alternative Exporting Methods - Brady, Donald L.; Bearden, William O. (Journal of International Business Studies, 1979)
The salient attributes of direct and indirect exporting methods of distribution were identified. Attitudes of three groups of executives (executives using direct exporting methods, executives using indirect exporting methods, and nonexporting executives) were assessed towards the attributes. Attitudes were analyzed using ANOVA. The findings suggest that the three groups of executives hold significantly different attitudes about the attributes. The findings (1) imply that executives using indirect exporting methods and nonexporitng executives are most alike in their attitudes; (2) offer an explaination for the tendency of executives to begin exporting with indirect methods and to switch to direct methods as exporting experience increases, and (3) identify the attitudes that each group of executives is most likely to hold.